CURRENT TREATMENT OF ACUTE BACTERIAL DESTRUCTIVE PNEUMONIA IN CHILDREN - E.E. Kobilov; M. K. Tukhtaev (Scholar Express Journals, 2022)
The paper presents data on the examination and treatment of 243 patients with acute destructive pneumonia. Based on this, an immunological rapid method for determining the type of pathogens of acute destructive pneumonia was developed based on the registration of antigen-binding lymphocytes (ASL) in the blood of patients that selectively react with bacterial antigens, which has significant advantages over traditional bacteriological research. A differentiated method of drainage treatment of severe pleural complications of acute destructive pneumonia in children was tested, which allows obtaining a more pronounced clinical effect compared to traditional treatment.
Keywords: acute destructive pneumonia; rapid immunological method; antigen-binding lymphocytes